What have we learnt about rotavirus in Spain in the last 10 years? - Javier Díez-Domingo; María Garcés-Sánchez; Francisco Giménez-Sánchez; Javier Colomina-Rodríguez; Federico Martinón-Torres (Elsevier, 2019)
Introduction: Vaccines against rotavirus (RV) have been available in Spain since 2006, but they are neither recommended nor financed by the National Health System. Nevertheless, through recommendations of the Spanish Association of Paediatrics vaccination has achieved intermediate coverage. Material and methods: A systematic literature review was performed on studies carried out in Spain in the last 12 years (2006-2018) on RV infection and vaccination. Results: A total of 43 studies were identified that met the inclusion criteria. The disease burden in children less than 5 years in the Primary Care setting ranged from 15 to 19 cases per 1000 children, and between 120 and 480 cases per 100,000 in the hospital setting, which has a significant economic and social impact. Vaccines against RV have shown an effectiveness of between 83% and 96%, and an impact of up to 70% in reducing hospital admissions, which is dependent on the achieved vaccine coverage. New research lines are identified, such as the role of the rotavirus vaccine and protection against seizures or the impact on the gut microbiota. Conclusions: The current available information supports the significant burden of rotavirus disease in Spain and the high effectiveness of the available vaccines. This evidence should allow for an updated re-evaluation of the national recommendations on rotavirus vaccination. Resumen: Introducción: En España, las vacunas frente a rotavirus (RV) están disponibles desde 2006 pero no están ni recomendadas ni financiadas por el Sistema Nacional de Salud. Sin embargo, a través de las recomendaciones de la Asociación Española de Pediatría se han alcanzado coberturas de vacunación intermedias. Material y métodos: Se ha realizado una revisión sistemática de la literatura sobre los estudios realizados en España en los últimos 12 años (2006-2018) en relación con la infección y las vacunas frente a RV. Resultados: Se identifican 43 estudios que cumplían los criterios de selección. La carga de enfermedad en población <5 años en atención primaria oscila entre 15 y 19 casos por 1.000 niños y en hospitalaria entre 120 y 480 casos por 100.000, lo que supone una importante repercusión económica y social. Las vacunas frente a RV han mostrado en España una efectividad de entre el 83 y el 96% y un impacto de hasta un 70% de reducción de hospitalizaciones, que es dependiente de la cobertura de vacunación alcanzada. Se identifican además nuevas líneas de investigación relacionadas con el papel de la vacuna del RV y la protección frente a convulsiones, o el papel del microbiota, entre otros. Conclusiones: La información actualmente disponible refrenda la importante carga de enfermedad por RV en España y la elevada efectividad de las vacunas disponibles. Estas evidencias permiten una reevaluación de las recomendaciones nacionales sobre vacunación frente a RV.